An effective device design for thermal management of multifinger InGaP/GaAs collector‐up HBTs. (7th February 2013) - Tseng, H. C.; Chen, J. Y.; Chou, J. H.
SUMMARY: An effective device structure for thermal management of multifinger InGaP/GaAs collector‐up heterojunction bipolar transistors (HBTs), compelling active components in high‐efficiency handset power amplifiers, is presented for the first time. From the unique 3‐D thickness‐adjusting numerical analysis, based on a finite element model, the miniaturized device can lead to a greater than 40% reduction in the thickness of plated gold layer. Above all, this is quite different from previous attempts, in which the thermal resistance was reduced by increasing the thickness of plated gold layer. Compared with literature works, the thermally stable design with an innovative heat‐spread configuration shows a 50% reduction in thermal resistance and demonstrates favorable power performance. Copyright © 2013 John Wiley & Sons, Ltd.